Like father, like son: Occupational choice, intergenerational persistence and misallocation - Salvatore Lo Bello; Iacopo Morchio (Quantitative Economics, 2022)
We develop a dynamic quantitative model of occupational choice and search frictions with multiple channels of intergenerational transmission (comparative advantage, social contacts, and preferences), and use it to decompose the occupational persistence observed in the UK. In the model, workers who choose their father's occupation find jobs faster and earn lower wages, which is consistent with patterns found in UK data. Quantitatively, parental networks account for 79% of total persistence. Shutting down parental networks or the transmission of preferences improves the allocation of workers, and thus yields welfare gains, while removing the transmission of comparative advantage generates welfare losses.
Keywords: J24; J62; J64; 330; Comparative advantage; labor productivity; mismatch; occupationalmobility; social contacts